COVID-19 Preventive Measure: A Study on “MASK-A Boon or a Bane” - Amin, Revati; Ghosh Dastidar, Ranita; K, Vaishali (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Background. Mask wearing can restrict the spread of respiratory viral transmission during the third wave of the COVID-19 pandemic. Globally, governments have emphasized its use in workplaces and public areas to prevent the transmission routes of corona virus. In spite of the current awareness in the general population, the stringency of wearing the mask lies as an individual’s choices. Subject and Methods. This research work discusses available studies on the types and comparison of masks in the market for use. It includes a short survey conducted with 1,173 anonymized healthy participants primarily devoid of comorbidities. The survey includes the effects of mask wearing, while outdoor with minimal activities like walking and with mild activities like jogging and stretching. Our research further discusses various health effects of wearing a mask, including cardiac output, hypoxemia, hypoxia, and dyspnoea, and how such situations that pose a threat can be consciously avoided. Results. It was found that the majority of people use cloth/fabric reusable mask. There remains scope for better-designed masks and improving health in the mass population by inculcating healthy breathing habits and other relevant exercises that can help people cope up better in this fight against the deadly virus at a larger scale. Conclusion. For most of the survey questions, there was significant correlation between gender and the related responses as there was no significantly observable difference in the nonparametric, unpaired analyses of responses. The main objective of this research work is to initiate more discussions and enhance awareness in natural ways of staying healthy during the pandemic emphasizing mask use. Further progress in this aspect remains a whole new area for future exploration.